DISORDERS OF THE INTESTINAL MICROBIOTA IN INFANTS: HOW THE RISK OF DEVELOPING ALLERGIC REACTIONS (Modern education and development, 2024)
Despite numerous works devoted to the formation of the intestinal biocenosis of newborns, differentiated approaches to assessing the severity and methods of correction have not been developed . Therapeutic tactics are constantly being improved, new drugs are being sought, corrective treatment is required to influence dysbiosis , which maintains recurrence and chronicity. atopic dermatitis.Prevention of dysbiosis in newborns and methods of its correction are one of the main tasks in pediatrics. For the same reason, in this work we studied the disturbance of intestinal microflora and its connection with allergic reactions.